The Influence of Book Tax Gap and Sharia-Compliant Tax Planning on Profit Persistence in Halal Consumer Goods Companies Listed on the Indonesian Stock Exchange - Suprihatin, Ade; Adha, Egi Nuansa; Ikram, Syafrizal (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to determine the effect of Book Tax Gap and Tax Planning on Profit Persistence which is moderated by Profit Quality in Consumer Good Industry (Consumer Non-Clycicals) companies listed on the IDX in 2020. Data collection techniques use descriptive methods and verification methods with the sampling technique purposive sampling with the technique taken, namely determining the sample with certain criteria. The type of data used in this study is secondary data with data taken in the 2020 period. Data analysis was carried out by testing the regression model with the classical assumption test followed by hypothesis testing. Based on the results of the analysis with a significance level of 5%, it shows that partially the Book Tax Gap and Tax Planning variables have a significant effect on the Profit Persistence variable. The Book Tax Gap variable, which is moderated by the Profit Quality variable, has no significant effect on the Profit Persistence variable.